2020
DOI: 10.1523/jneurosci.1091-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

LAR-RPTPs Directly Interact with Neurexins to Coordinate Bidirectional Assembly of Molecular Machineries

Abstract: Neurexins (Nrxns) and LAR-RPTPs (leukocyte common antigen-related protein tyrosine phosphatases) are presynaptic adhesion proteins responsible for organizing presynaptic machineries through interactions with nonoverlapping extracellular ligands. Here, we report that two members of the LAR-RPTP family, PTPr and PTPd, are required for the presynaptogenic activity of Nrxns. Intriguingly, Nrxn1 and PTPr require distinct sets of intracellular proteins for the assembly of specific presynaptic terminals. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…Overall, we demonstrate that ablation of LAR-RPTPs from vertebrate synapses does not alter synapse density, vesicle docking, membrane anchoring of active zones, and synaptic vesicle release. This aligns with a parallel study that reported no loss of synaptic puncta and efficient release at excitatory synapses in cultured hippocampal neurons and in acute hippocampal brain slices (Sclip and Südhof, 2020) upon LAR-RPTP knockout, but contrasts RNAi-based studies that led to models in which these RPTPs are major synapse organizers (Dunah et al, 2005; Fukai and Yoshida, 2020; Han et al, 2018, 2020a, 2020b; Kwon et al, 2010; Takahashi and Craig, 2013; Um and Ko, 2013; Yim et al, 2013). LAR-RPTPs belong to the superfamily of RPTPs (Johnson and Van Vactor, 2003), and it is possible that different RPTPs compensate for their loss.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Overall, we demonstrate that ablation of LAR-RPTPs from vertebrate synapses does not alter synapse density, vesicle docking, membrane anchoring of active zones, and synaptic vesicle release. This aligns with a parallel study that reported no loss of synaptic puncta and efficient release at excitatory synapses in cultured hippocampal neurons and in acute hippocampal brain slices (Sclip and Südhof, 2020) upon LAR-RPTP knockout, but contrasts RNAi-based studies that led to models in which these RPTPs are major synapse organizers (Dunah et al, 2005; Fukai and Yoshida, 2020; Han et al, 2018, 2020a, 2020b; Kwon et al, 2010; Takahashi and Craig, 2013; Um and Ko, 2013; Yim et al, 2013). LAR-RPTPs belong to the superfamily of RPTPs (Johnson and Van Vactor, 2003), and it is possible that different RPTPs compensate for their loss.…”
Section: Discussionsupporting
confidence: 83%
“…1L-1O), consistent with enlargements observed in invertebrates (Ackley et al, 2005; Kaufmann et al, 2002). A recent independent study that ablated LAR-RPTPs early also found normal synapse densities (Sclip and Südhof, 2020), contradicting the generalized model that LAR-RPTPs are master synapse organizers (Dunah et al, 2005; Fukai and Yoshida, 2020; Han et al, 2018, 2020a, 2020b; Kwon et al, 2010; Takahashi and Craig, 2013; Um and Ko, 2013; Yim et al, 2013). It remains possible that LAR-RPTPs control assembly of a specific subset of synapses, which may explain why PTPδ ablation causes modest layer-specific impairments of synaptic strength (Park et al, 2020).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent study revealed that HS moiety of Nrxs not only bound to the postsynaptic Nlgns and LRRTMs, but they also formed complexes with the presynaptic synapse organizer, PTPσ ( Figure 1A ) ( Han et al, 2020 ; Roppongi et al, 2020 ). LRRTM4 bound with Nrx through HS, but not with PTPσ.…”
Section: Functions Of Vertebrate Glypicans At Synapsesmentioning
confidence: 99%